The principle of community in Kant: conceptual and concrete dimensions of sensus communis - Ferreira, Pedro Gallina (Studia Kantiana, 2025)
In this paper, I analyze the possible political significance that Kant’s concept of the faculty of judgment <Urteilskraft> acquires when articulating abstract rules and concrete circumstances so as to reflect from a universal standpoint. Such a procedure is intrinsic to theoretical and practical interests of human reason in determining particular representations according to the transcendental categories of understanding and the ideas of pure reason. My goal is to explore the communal aspect of this universal perspective of judgment and of its development. Although Kant did not write about a theory of community, I argue that an investigation of his conception of sensus communis can provide a fruitful approach to the collective dimension of his “architectonic of reason”. I aim to show that common sense and social reciprocity should work as a substrate to political judgment as far as they are considered the result of a transcendental idea of community.